Pronunciation of Malay words among slow learners using clinical linguistics analysis - Abd. Nasir, Siti Noridayu; Abdul Halim, Hazlina; Yahaya, Ahmad Shuib; Kamaruddin, Rohaidah (University of Malaya, 2022)
Slow learners often face issues when learning their first language. Since Malay is the functional language in Malaysia, students need to master it to facilitate the process of teaching and learning. However, poor vocabulary when speaking in the first language could affect the communication process, as seen among students who are slow learners. Therefore, this study aimed to examine the subjects’ pronunciation of various Malay words using posters and identify speech errors using clinical linguistics. Subsequently, the paper discussed the link between pronunciation and B. F. Skinner’s behaviourist theory of learning involving positive and negative reinforcement. Results showed that there was still incoherent pronunciation despite the subjects being 16 years old. However, after positive reinforcement, the subjects appeared more confident and spirited in pronouncing specific words correctly. The subjects also stumbled with 11 out of the 60 words tested. Standard pronunciation was also influenced by the dialects of their respective home states. On that account, continuous support and practice should be emphasised to encourage students to enunciate better. In future, this study could catalyse further research in the field of clinical linguistics on slow learners in Malaysia.